Discussion of Learning: Implementation and Effect on Critical Thinking Skills of Students in General Physics Courses - Titin Sunarti; Mohd Zaidi Bin Amiruddin; Wasis; Woro Setyarsih; Mukhayyarotin Niswati Rodliyatul Jauhariyah; Abu Zainuddin (Indonesia Approach Education, 2023)
This study aims to determine the effect of applying the learning discussion model on students' critical thinking skills. This study uses a type of pre-experimental research with a research design, one group pretest-posttest design. The subjects of this research are students who program general physics courses from chemistry study program, biology study program, and mathematics study program. This research tested by giving pretest questions, treating discussion learning models, and posttest in general physics courses. The results of this study found that critical thinking skills students are the highest student (1) study program mathematics, (2) biology study program, and (3) chemistry study program. In addition, test results and learning each has a relationship with the other, proven by paired sample t-tests. That way, critical thinking skills are essential for students to master to compete in the era of technological development and the demands of the 21st century. Critical thinking skills are not seen from the department but from the ability of each individual in solving problems.